Persepsi atas Kompetensi Pedagogik Guru dan Minat Berpengaruh terhadap Prestasi Belajar Ilmu Pengetahuan Sosial Siswa SMP Negeri di Kabupaten Bekasi - Walujo Usodo; Sumaryoto Sumaryoto; Heru Sriyono (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
The research objective was to determine 1) The effect of perceptions on teacher pedagogic competence and mutual interest on the learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. 2) The effect of perceptions on teacher pedagogical competence on learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. 3) The influence of interest on the learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. The method used in this study is a survey method with multiple linear regression correlational techniques with a sample size of 90 students. The results showed: 1) There is a significant influence of perceptions of teacher pedagogical competence and interest together on the learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. This is evidenced by the acquisition of the Sig. = 0.000 <0.05 and Fcount = 19.734. 2) There is a significant influence on perceptions of teacher pedagogical competence on the learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. This is evidenced by the acquisition of the Sig. = 0.008 <0.05 and tcount = 2,696. 3) There is a significant influence of interest on the learning achievement of Social Science students of State Junior High Schools in Bekasi Regency. This is evidenced by the acquisition of the Sig. = 0.000 <0.05 and tcount = 3.689.